2009
DOI: 10.1007/s00280-009-1045-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase inhibitors emodin and dichloro-ribofuranosylbenzimidazole modulate the cellular accumulation and cytotoxicity of cisplatin in a schedule-dependent manner

Abstract: Purpose Protein kinase inhibitors (PKI) have become prominent agents in cancer therapeutics. However, the specificity for target kinase inhibition can be poor and unwanted effects can emerge in combination regimens. The PKI emodin, for instance, can produce mixed results when combined with cisplatin, and we have sought a biochemical pharmacologic explanation for the negative cytotoxic effects. Methods Human ovraian A2780 tumor cells were exposed to the PKI emodin or dichloro-ribofuranosylbenzimidazole (DRB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In an earlier study, the protein kinase inhibitors emodin and dichlororibofuranosylbenzimidazole, which are structurally similar to sorafenib, were found to decrease cisplatin uptake and DNA platination. The effect was, however, abrogated by CTR1 knockdown (40). Sorafenib modulation of CTR1 expression may be mediated through inhibition of MAPK signaling as the MEK inhibitor U0126 had a similar effect.…”
Section: Discussionmentioning
confidence: 92%
“…In an earlier study, the protein kinase inhibitors emodin and dichlororibofuranosylbenzimidazole, which are structurally similar to sorafenib, were found to decrease cisplatin uptake and DNA platination. The effect was, however, abrogated by CTR1 knockdown (40). Sorafenib modulation of CTR1 expression may be mediated through inhibition of MAPK signaling as the MEK inhibitor U0126 had a similar effect.…”
Section: Discussionmentioning
confidence: 92%
“…However, emodin exerts a downregulatory effect on Mdr-1 protein in prostate cells, with over-activated HiF-1 and potent Mdr (9). in previous studies, emodin has been shown to synergize with cisplatin (29,30), paclitaxel (6) and celecoxib (31), leading to an enhanced antiproliferation effect in several cancer cell lines. Therefore, we hypothesized that emodin combined with gemcitabine may also have a synergistic effect on pancreatic cancer cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Cisplatin has been previously shown to be potentiated by other polyphenols such as emodin, in non-small cell lung cancer (NSCLC) with HER-2/neu-overexpressing [28], merkel cell carcinoma (MCC) [29], human ovarian tumour cell lines (A2780) [30], and gallbladder carcinoma cells (SGC996) [31, 32]. Likewise, here cisplatin and cyclophosphamide in combination with quercetin synergistically reduced ATP levels, induced apoptosis, and accumulated the cells at S phase and/or G 2 /M phase in both lymphoid and myeloid cell lines.…”
Section: Discussionmentioning
confidence: 99%